Innovative Puzzle-Based Assessment in Arabic Language Learning for Enhancing Vocabulary Mastery - Zahra Shafirah Ambo; Najwa Bil Qhisti; Tasya Khoirunnisa Ambo (Al Maghazi : Arabic Language in Higher Education, 2026)
Arabic teachers find it difficult in the learning process. This is because the students are still minimal in mastering Arabic vocabulary. This study aims to examine the effectiveness of innovative puzzle based assessment in enhancing Arabic vocabulary master among seventh grade students at MTsN 1 Unaaha. Using a quantitative approach with a quasi experimental design, the study involved seven grade students who participated in puzzle based assessment activities integrated into Arabic language learning. Data were collected through pretest, posttests, observations, and student feedback. The results indicated that puzzle based Arabic language assessment was effective, with an effectiveness rate of 68%. It significantly improved students Arabic vocabulary mastery while increasing their motivation, engagement, and active participation throughout the assessment process. The study contributes to the growing literature on innovative and authentic assessment by demonstrating how game based assessment can simultaneously evaluate and reinforce learning. Future research is recommended to investigate the application of puzzle based assessment across different language skills, educational levels, and learning contexts.